Corporate Governance and Sustainability in Islamic Banking: The Mediating Role of Green Banking Practices - Candera, Mister; Ridhwan, Muhammad; Masdaini, Efrina; Mahendra, Aditya Teguh; Apriandika, Rico (Sekolah Tinggi Agama islam Negeri Majene, 2025)
The banking sector plays a strategic role in advancing sustainable business practices through green banking initiatives, which reduce environmental risks and enhance banks’ reputations amid growing global concerns about climate change. This study examines corporate governance and sustainability performance in Islamic banks, with green banking as a mediator. The data were collected from 158 middle and upper management employees in Islamic banking institutions in South Sumatra, Indonesia. This study used mediation path analysis to assess the effect of corporate governance on sustainability performance directly and through green banking practices indirectly. The results confirm a positive relationship between corporate governance framework and sustainability performance in Islamic banks, suggesting that strengthening governance structures directly improves sustainability outcomes. Moreover, green banking practices partially mediate the nexus between corporate governance and sustainability performance, indicating that corporate governance indirectly improves sustainability performance by promoting green banking initiatives. These findings show the necessity of aligning corporate governance frameworks with green banking initiatives to achieve long-term sustainability goals in Islamic banking.